THE ECONOMIC MECHANISM OF THE MICRO-LEVEL STRATEGIC DEVELOPTMENT OF THE INDEPENDENT REGION - Tkachuk, I.H.; Melnychuk , Yu.M. (The actual problems of regional economy development, 2019)
The article “The Economic Mechanism of the Micro-level Strategic Development of the Independent Region” is aimed at exploring territorial communities as the founder of the creation of an independent region in Ukraine. The purpose of the article is to explore the basic provisions of the mechanism of self-government and self-financing of united territorial communities as prerequisites for the creation of an independent region. The work used a set of research methods, which is the methodology of analysis and organization of major publications, legislation and laws, namely methods of generalization, comparison, chronologization, analysis and generalization. The article deals with the concept of "territorial formation", which allows to fully grasp the value of territorial communities in the formation of an autonomous region, identifies the value of territorial ownership. The results of the study were conclusions made on the basis of research into the scientific and legislative base of research on this issue, as well as the formation of the main features of an independent region, which formed a scientific novelty in the field of economic research. The practical importance of scientific research and its results is the model of economic mechanism. The model should be dominated by the concept of economic equality of all subjects and parties to ownership. It is this system of economic relations between the center and the region that aligns the initial conditions, which sufficiently stimulates both subjects of property relations.